Determinants of Taxpayer Compliance: The Roles of Understanding, Socialization, System Implementation, and Sanctions - Kursillah, Dhea Ajeng; Dwiati, Agustina Ratna (E-Jurnal Akuntansi, 2024)
This research was motivated by instances of fraudulent tax reporting by corporate taxpayers in Gresik Regency. The study aims to test and examine the influence of tax law knowledge, tax socialization, modern administrative systems, and tax penalties on taxpayer compliance. The population for the study consisted of cooperative taxpayers registered with the Trade, Industry, and Micro, Small, and Medium Enterprises Cooperative Office in Gresik Regency, totaling 763 taxpayers. Using a probability sampling method, a sample of 88 respondents was selected, determined using the Slovin formula. The researchers employed hypothesis testing using the Structural Equation Model (SEM) method with SmartPLS software. The results indicate that understanding tax regulations, tax socialization, and modern administrative systems have a strong positive impact on taxpayer compliance. However, tax penalties were found to have a relatively negative influence on compliance.